RANCANG BANGUN APLIKASI PERAMALAN PERMINTAAN PADA TOKO ROTI YULIA BAKERY KEDIRI - Puspasari, Lilia; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Yulia Bakery is one of the bakeries in Kediri. The problems happens when there is a customer who wants to buy bread, but bread available at the store did not meet. This can lead to disappointment on the customer, so that Yulia Bakery can lose customers. This happens because in determining demand, Yulia Bakery has not been able to use the calculation of demand but only based on estimates. The problem can be solved by calculating demand forecasting based on sales data in the previous period. Forecasting calculations using the method of Naive and Exponential Smoothing Winter because this method fits with the pattern of existing data. The method used can forecast demand for the next two periods. Based on trial results and the evaluation shows that forecasting application that has been created can perform calculations using two methods of forecast. The best forecasting value used is selected from a method that has a relatively small error values using Exponential Smoothing Methods Winter. Applications can predict future demand for the two periods with an error value of 106.881. Keywords: Demand Forecasting, Exponential Smoothing Winter, Naive